PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER MODEL TUTORIAL INTERAKTIF PADA MATERI POKOK PENYAJIAN DATA KELAS VII - Nurul Hidayati; Yenita Roza; Syarifah Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This Research aimed to develop a valid computer based interactivelearning media to help studentslearn the subject of data presentation. This researchuses development modelof Borg and Gall modified by Sugiyono, the following stagesare: (1) potential and problem; (2) collect information; (3) product design; (4) designvalidation; (5) design revision; (6) product testing; (7) product revision; (8) usagetesting; and (9) product revision. At the stage of potential and problem, researchermade a needs analysis of observation and interviews with Mathematics teacher andstudents. Then, researcher collected the informations by conducting literature studies.Product design is through two stages, by making paper based design and then computerbased design that used Microsoft Power Point. The learning media is validated by threevalidators used validation instrument and obtained an average score of 3,55 (veryvalid). Then the product revised based on the input from validators. The revision oflearning media was tested by questionnaire technique using student responsequestionnaire. The testing was conducted through two stages,which are small groupconsist of six students of grade VII and a large group consist of 28 students class ofVII.6 MTs Negeri 1 Pekanbaru. The product of computer-based interactive learningmedia is already practiced with an average of 96,03% (very practice)in a small testgroup and 97,62% (very practice) in the large group test. Then the product revisedaccording to the student's suggestion on questionnaire. Thus, it can be concluded thatcomputer based learning media is valid and practical.Key Words : Computer-based Interactive Learning Media, Development, Data Presentation